hythmic Deletion in Hassan ‘Arbash’s Poetry (Journal of Hama University, 2021)
The poet Hassan ‘Arbash is one of the distinctive poets of Hama City, who have been writing classical poetry. Nevertheless, he has the talent of writing poetry using the classical meters without commitment to the number of foot of each meter and with distributing of it away from using the line of two parts.This research is an attempt to shed light on the this experience from the perspective of deleting the foot, and to show to what extent this might affect the poem and the Rhyme by it. It also shows how much this does not rely on the common meters and their number. It also reflects how the poet behave in dividing it depending on the visual rhythm and the agreement between all this and the poetic experience. This is the first aim of this research. As far as the second aim, I try to follow up the exceptions and the features adopted for this deletion and the poetic exceptions and how the poet has been obliged to resort to use them and the causes for their use and their effect on meaning and meter and pace.